THE IMPACT OF DIGITALIZATION ON INDUSTRY RISKS (EXEMPLIFIED BY TRANSPORT) - I. V. Anokhov; O. N. Rimskaya (Стратегические решения и риск-менеджмент)
Today, digital transformation has become a strategic development priority for many advanced industries, including transportation. There are high expectations for cost reduction, increased product quality consistency, and improved manageability of production as a whole. However, the optimistic expectations of many executives do not take into account the changing industry risks that can seriously affect the outcome of digitalization.The purpose of this article is to investigate the impact of the digitalization process of transport on related industry risks. The theoretical basis of the article is universal organizational science of A. Bogdanov. The object of the study is freight transport.The article argues that industry risks can be classified into three subrisks: subrisks associated with industry technology; subrisks of coordination of interests of participants in the transport process; subrisks of the transporter to manage the long-term behavior of freighters and consignees. Quantitative models characterizing each of these subrisks are proposed.This approach is tested with three examples: The Northern Sea Route, railway transport in Russia, and the sea route from South-East Asia to Europe. The actual subrisk and the quantitative level for each of these objects are determined. It is stated that a radical change in the level of risk is possible primarily with the help of digital technology. At the same time, digitalization gives rise to fundamentally new risks, the main of which is the risk of exhausting the differences that have caused macroeconomic flows till now.This article is a logical continuation of the article written by the authors I. Anokhov and O. Rimskaya “Digital twins and their application in transport economy”, published in № 2.2021 in the journal “Strategic decisions and risk management”.